2003
DOI: 10.1111/j.1463-1318.2004.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled clinical trial of stapled haemorrhoidectomy vs conventional haemorrhoidectomy; a three and a half year follow up

Abstract: It will be important to review the long-term results of larger trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 5 publications
4
53
1
7
Order By: Relevance
“…However, in the recent literature, a significant incidence of recurrence after stapled hemorrhoidopexy was reported. In studies evaluating stapl ed hem orrhoid opexy and conventional hemorrhoidectomy for Grade III and IV hemorrhoids with an adequate and systematic follow-up (>1 year), the incidence of recurrence was 0 to 26 % and 0 to 10.8 %, respectively; reoperation rate was up to 16.7 % after stapled hemorrhoidopexy [43,46,61,[63][64][65][70][71][72]. After conventional Ferguson's hemorrhoidectomy, a redo surgery for recurrent hemorrhoids was necessary in 0.8 % of cases in a large series [73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the recent literature, a significant incidence of recurrence after stapled hemorrhoidopexy was reported. In studies evaluating stapl ed hem orrhoid opexy and conventional hemorrhoidectomy for Grade III and IV hemorrhoids with an adequate and systematic follow-up (>1 year), the incidence of recurrence was 0 to 26 % and 0 to 10.8 %, respectively; reoperation rate was up to 16.7 % after stapled hemorrhoidopexy [43,46,61,[63][64][65][70][71][72]. After conventional Ferguson's hemorrhoidectomy, a redo surgery for recurrent hemorrhoids was necessary in 0.8 % of cases in a large series [73].…”
Section: Resultsmentioning
confidence: 99%
“…In most patients, incontinence is transitory, due to excessive anal stretching secondary to circular anal dilator insertion [62]. At long-term follow-up, persistent continence problems were reported in a minority of patients with no significant difference with respect to conventional hemorrhoidectomy [61,[63][64][65]. Similarly, fecal urgency is a common complication especially soon after stapled hemorrhoidopexy.…”
Section: Complicationsmentioning
confidence: 99%
“…The rate of bleeding reportedly ranges between 5% and 85% [9,13,17,22] . The rates of bleeding in the PA group and in the MA group in the present study were 33.3% and 31.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with a stapler line uniformly 22 mm above the dentate line needed fewer postoperative narcotic analgesics and returned to work earlier [1] . In the case of an incomplete donut or a donut with thin parts, this may increase the risk of bleeding during the early postoperative period or recurrence in the late period [17] . Various modifications of the purse-string anoscope have been used for easier application of the suture and a new anoscope has been designed [10][11][12]18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…DVSC procedures represent an easy way of treating hemorrhoids leading to immediate arrest of bleeding, regression in size of prolapsed hemorrhoidal cushions, it is a day case surgery, less complicated, easy to perform, and does not require a special needs such as Doppler sounder or expensive stapler instruments [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%